IMPLEMENTASI KURIKULUM EDUTECHNO PRENEURSHIP ISLAMI DI SMK NEGERI 3 LHOKSEUMAWE: PEMBENTUKAN KARAKTER DAN PENINGKATAN KOMPETENSI PESERTA DIDIK - Muklir, Muklir; Hasyem, Muhammad; Abdullah, Abdullah; Alfiady, Teuku; Murniati, Murniati (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
This study aims to understand the implementation of the Islamic Edutechno Preneurship Curriculum at SMK Negeri 3 Lhokseumawe and its impact on character building and skill enhancement of students. Using qualitative methods, including in-depth interviews, observations, and document analysis, the research involved various stakeholders at the school. Results show that SMK Negeri 3 Lhokseumawe has established a School Development Team (TPS) to implement strategic steps in applying this curriculum. Programs such as Mandatory Scouting (Wapra) and Islamic Spirituality (Rohis) are integral to these efforts, focusing on the development of Islamic character and the integration of noble moral values in every lesson. Teacher competency is enhanced through In-House Training and Workshops, aiding in the development of both pedagogical and professional skills. The curriculum's implementation is also supported by the Aceh Education Department's socialization efforts. However, challenges remain, such as insufficient cooperation among teachers in enforcing discipline and the lack of textbooks integrated with the new curriculum. Overall, the implementation of the Islamic Edutechno Preneurship Curriculum at SMK Negeri 3 Lhokseumawe shows positive development. This curriculum has great potential to improve students' skills and Islamic character, preparing them for future challenges. This study provides valuable insights for the development of character-based and technopreneurship curricula in vocational education settings.